Green Roof Analysis and Design Software Calculator in Egypt - Mostafa El-Ahwal; ashraf elmokadem; Dalia EL-Gheznawy; Naglaa Megahed (Port Said Engineering Research Journal, 2016)
Green Roofs Analysis and Design software (GRAD) 1st version is a data-base-driven tool, which has been developed from detailed green roofs sections calculation at residential buildings according to the Egyptian climate zones, and Egyptian energy code. The goal was to create an easy tool that enabled architects, developers, and others to ease the process of green roof sections use and selection. In addition to obtain quick estimates of how green roof design decisions might impact building energy use and design decisions. The Green Roofs Analysis and Design program performs the green roof sections within a database of 784 green roof sections, which has been designed at a previous stage, to estimate the residential roof building energy reduction in Egypt. The outputs from each user provide basic characteristics of a green roof project; produces information for two green roof systems (built-in system, module system). The program can be used in the design and analysis of green roofs sections in Egypt; and also the software program can be used to compare the impact of different variables which effect on buildings thermal behavior